b - Shapiro, Norma; Lanzano, Susan; Jensen, Lynn (New York : Oxford University Press, 1998)
A comprehensive, flexible, and up-to-date vocabulary reference and teaching tool for English language learning. The Oxford Picture Dictionary and its components create a highly teachable programme that can be used as a complete, four-skills beginning course, or as a language development supplement and practical reference.
Keywords: Picture dictionaries, English -- Non-fiction; English languages-textbooks for foreign speaker -- Non-fiction